MODERN PROGRESS OF EVENTFUL TOURISM TRENDS ІN ZAKARPATTIA - PANKIV, NATALIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Theoretical principles and history of study of eventful tourism, his classification, and also modern state of this sphere, are considered in the article. Progress of eventful tourism trends are analysed on Zakarpattia and it is set that during the last years there are positive tendencies in relation to their development, in particular: the specialized tour operators that offer corresponding tours and the new objects of eventful  rest are opened appear. It is educed that Zakarpattia is extraordinarily rich in traditions and ethnic colour and has considerable advantages for development of eventful tourism, as here is considerable tourist-recreational potential. In villages and small towns Zakarpattia the most various and interesting festivals and holidays pass that, it is possible conditionally to divide into three groups-guilty, gastronomic and folklore. Lately large popularity was purchased by the tours of flowers on Zakarpattia.Eventful tourism is perspective on Zakarpattia, with inexhaustible resource potential, and the programs of festivals are saturated, original and interesting and profitable. They assist to socio-economic development of area, popularization of potential tourist resources among a population. Important pre-condition of organization of festival tourism is the timely informing and advertising of events, popularity to information about her and organization of her systematic realization. Most permanent festivals have own web-sites, on that there is information about realization and program of measures, tourist infrastructure, transport report. Forming of positive image of region and increase of amount of tourists is assisted by tourist-informative centers that accumulate information about tourist-recreational suggestions.Without regard to plenty of festivals international status is had only separate from them. Therefore, in order to attract the attention of tourists to Zakarpattia, it is expedient to create the government program of assistance and development of festival motion and distinguish the regional centers of festival tourism. Such regional centers can be cities that are selected on the principle of scale and the possibility of representation of an event. Such centers in the region can be Uzhgorod, Beregovo, Rakhiv, Mukachevo.
Keywords: tourism; eventful tourism; Zakarpattiа